2015
DOI: 10.1002/cne.23871
|View full text |Cite
|
Sign up to set email alerts
|

From sauropsids to mammals and back: New approaches to comparative cortical development

Abstract: Evolution of the mammalian neocortex (isocortex) has been a persisting problem in neurobiology. While recent studies have attempted to understand the evolutionary expansion of the human neocortex from rodents, similar approaches have been used to study the changes between reptiles, birds, and mammals. We review here findings from the past decades on the development, organization, and gene expression patterns in various extant species. This review aims to compare cortical cell numbers and neuronal cell types to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 97 publications
3
58
1
Order By: Relevance
“…1A) (23). In each species, we examined three time points spanning critical events of corticogenesis, including the emergence of multiple transient proliferative embryonic zones in the dorsal pallium, which may be a mammal-specific characteristic; genesis and migration of cortical neurons; and initiation of neuronal connections (17,22,28). To infer neocortical enhancers that were likely active in the mammalian stem lineage, we identified enhancer regions in human and mouse that showed reproducible activity in both species based on epigenetic signatures (Fig.…”
Section: Defining a Set Of Neocortical Enhancers Exhibiting Conservedmentioning
confidence: 99%
See 1 more Smart Citation
“…1A) (23). In each species, we examined three time points spanning critical events of corticogenesis, including the emergence of multiple transient proliferative embryonic zones in the dorsal pallium, which may be a mammal-specific characteristic; genesis and migration of cortical neurons; and initiation of neuronal connections (17,22,28). To infer neocortical enhancers that were likely active in the mammalian stem lineage, we identified enhancer regions in human and mouse that showed reproducible activity in both species based on epigenetic signatures (Fig.…”
Section: Defining a Set Of Neocortical Enhancers Exhibiting Conservedmentioning
confidence: 99%
“…Nonmammalian vertebrates lack the six-layered forebrain architecture that defines the mature neocortex (17,18). Adult structures derived from the dorsal pallium in birds and reptiles are vastly different from the neocortex at the structural, functional, and molecular level, complicating efforts to understand how the neocortex evolved (18)(19)(20)(21)(22). A recent study reported major transcriptomic divergence between the adult mouse neocortex and various chicken forebrain structures, supporting the hypothesis that mammal-specific regulatory functions contribute to the divergent morphology of the mammalian neocortex (20).…”
mentioning
confidence: 99%
“…sharks and rays, or ratfishes and chimeras), Osteichthyes (bony fishes divided into ray-finned fishes and the lobe-limbed vertebrates), Amphibia (amphibians represented by toads and frogs), Reptilia (reptiles: turtles, lizards, snakes) and Aves (birds) and Mammalia (mammals: opossums, mice, rats, cats) including Primates (primates: monkeys, apes, humans) correspond to the brains of our human ancestors from about 560 million years ago until the present (Moreno and González, 2011). A special position is taken by lungfish (a lobe-finned fish, closest ancestor of all tetrapods) and turtles as being comparable to ancient creatures which appear to be the most precisely positioned within this evolutionary line, while more recent reptiles and birds (sauropsids) appear to derive from another line of turtle-like ancestors rather than mammals (Butler et al, 2011; Moreno and González, 2011; Montiel et al, 2016). The very first vertebrate is considered to be an animal comparable with modern lamprey; this animal has a head containing a brain and has vertebrates, but not yet a lower jaw.…”
Section: Evolution To the Human Forebrainmentioning
confidence: 99%
“…However, this expansion occurred along different lines in non-synapsid (turtles, reptiles, birds) and synapsid (mammals) animals (36,37). The dorsal thalamus consists of two divisions called lemnothalamus and collothalamus.…”
Section: New Cerebral Capacities Of Mammalsmentioning
confidence: 99%